How to promote exclusive breastfeeding in Ireland: a qualitative study on views of Chinese immigrant mothers - Haoyue Chen; Cheng Li; Qianling Zhou; Tanya M. Cassidy; Katherine M. Younger; Siao Shen; John M. Kearney (BMC, 2021)
Abstract Background The exclusive breastfeeding rate in Ireland is very low with extremely slow annual growth. The population of immigrants in Ireland is increasing. Improving exclusive breastfeeding practice among immigrants may contribute to the overall improvement of exclusive breastfeeding rates in Ireland. This study was conducted to elicit suggestions on improving exclusive breastfeeding rate for the first 6 months among Chinese immigrants in Ireland. Methods Fourteen semi-structured in-depth interviews were conducted with Chinese immigrant mothers residing in Ireland, who breastfed exclusively for 4 to 6 months. Interviews were recorded and transcribed in Chinese. Data were analyzed using a qualitative thematic analysis. Themes were developed through categorization of codes and via in-depth discussion between two researchers. Results Themes generated from the thematic content analysis were: 1) suggestions for new mothers: being strong mentally and getting support from family and friends; 2) suggestions for employers: creating a supportive workplace by setting up private rooms and breastmilk storage facilities; 3) suggestions for healthcare professionals: advocating breastfeeding in the hospital and addressing cultural differences by recruiting multilingual staff; 4) suggestions for the government: promoting breastfeeding by initiating societal and policy changes. Conclusions The key findings emerging from this study may be considered in the development of breastfeeding promotion strategies in Ireland. Our findings could also have implications for other English-speaking countries with low rates of exclusive breastfeeding.